A case report of primary pleomorphic lung cancer with an atypical presentation - Kambampati, Sailaja; N. Ram Joshna; Prathipati, Roja Prasanthi; Patil, Anitha; Avanigadda, Sravani; Tourani, Vijaya (International Journal of Research in Medical Sciences, 2023)
Pulmonary pleomorphic carcinoma (PPC) is an uncommon primary lung tumor with a low incidence and aggressive biological characteristics that can occur in young people and nonsmokers. Pleomorphic carcinoma (PC) has a worse prognosis than other non-small cell lung tumors. We describe a 45-year-old man who complained of having a dry cough for a month. A well-defined mass in the anterior section of the left lower lobe was identified by chest high-resolution computed tomography (HRCT), and a positron emission tomography (PET) scan confirmed a left lobulated tumor with fluorodeoxyglucose (FDG) uptake in the left mediastinal lymph nodes. An endobronchial ultrasound guided transbronchial needle aspiration (EBUS TBNA) guided biopsy of the tumor was performed and sent for histopathological analysis, which identified pleomorphic squamous cells and giant cells. Positive IHC markers included P63, TTF1, pancytokeratin, Vimentin. Patient was diagnosed with stage IIIa (T3N2M0) pleomorphic carcinoma of the lung. Due to the tumor's advanced stage, the patient received chemotherapy and radiation therapy.